FORMATION OF THE EMPLOYER BRAND IN THE SYSTEM OF ENTERPRISE DEVELOPMENT MANAGEMENT - Salo, Salo Yana (Current Problems of Sustainable Development, 2026)
The article examines the theoretical and applied aspects of employer brand formation within the system of enterprise development management. The relevance of the study is determined by the increasing role of intangible factors in ensuring enterprise development, among which human capital and the instruments for its formation and effective utilization are of particular importance. In this context, the employer brand is considered as a significant element of the modern enterprise management system that influences its ability to adapt, grow, and build competitive advantages. The paper generalizes scientific approaches to defining the essence of the employer brand and clarifies its interpretation as an integrated intangible asset of the enterprise, formed through the interaction of internal management processes and external marketing communications. This approach makes it possible to expand the traditional understanding of the employer brand and to define its role within the enterprise development management system. The place of the employer brand within the system of enterprise development factors is identified, and its relationship with human, intellectual, and reputational capital is revealed. It is demonstrated that the employer brand contributes to the formation of a high-quality workforce, increases employee engagement, and creates conditions for the innovative development of the enterprise. The mechanism of employer brand formation is described, including analytical, strategic, and operational stages, as well as feedback as a tool for adaptation to changes in both internal and external environments. Particular attention is paid to the factors influencing the impact of the employer brand on enterprise development, which are considered as elements of a unified mechanism for transforming human capital into economic growth outcomes. The main directions of the employer brand’s impact on enterprise  development results are identified, including increased labor productivity, enhanced innovation activity, improved resource efficiency, strengthened competitiveness, and sustainable long-term development.
Keywords: employer brand; enterprise development management; enterprise development; personnel marketing; competitiveness